2003
DOI: 10.1097/01.tp.0000074722.79186.a9
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and treatment of chronic allograft nephropathy with everolimus

Abstract: Everolimus ameliorates CAN as a result of antiproliferative or apoptosis-enhancing effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 28 publications
0
28
0
1
Order By: Relevance
“…Regarding the previous studies of classical CAN in F344/Lewis rat models [2][3][4][5][6], mild focal mononuclear cell infiltration was observed at the 1st week post-transplantation, whereas at the 12th week, the disease was characterized by tubulointerstitial mononuclear cell infiltration and vascular intimal proliferation with proteinuria. The renal function became gradually impaired thereafter.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Regarding the previous studies of classical CAN in F344/Lewis rat models [2][3][4][5][6], mild focal mononuclear cell infiltration was observed at the 1st week post-transplantation, whereas at the 12th week, the disease was characterized by tubulointerstitial mononuclear cell infiltration and vascular intimal proliferation with proteinuria. The renal function became gradually impaired thereafter.…”
Section: Discussionmentioning
confidence: 67%
“…Total RNA was extracted from representative kidney samples using Trizol reagent (Gibco/BRL, USA) as previously described [2][3][4][5], and the samples were stored at -80°C until use. In brief, 60-100 mg of frozen tissue sample was homogenized in 1 ml of Trizol reagent, and 200 ll of chloroform was added to the homogenate.…”
Section: Total Rna Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…This attribute may represent an additional benefit of everolimus as these proliferative processes are implicated in the development of CAN in renal-transplant recipients and cardiac allograft vasculopathy in cardiac-transplant recipients, which are key causes of allograft dysfunction 11,12 Furthermore, animal studies have demonstrated that the antiproliferative effects of everolimus reduce long-term graft-specific histological changes, delaying the progression of CAN, even when already at an advanced stage. 13 Studies of sirolimus and everolimus drug-eluting stents further support the ability of this class of drugs to inhibit pathological vascular remodeling. 28,29 Taken together, these data suggest that the mechanism of action of everolimus appears to target the key cause of CAN.…”
Section: Antiproliferative Effectsmentioning
confidence: 99%
“…11,12 Animal studies have demonstrated that the antiproliferative effects of everolimus reduce long-term graft-specific histological changes, delaying the progression of CAN, even when already at an advanced stage. 13 Therefore, the mechanism of action of everolimus appears to target the key cause of CAN.…”
Section: Mechanism Of Actionmentioning
confidence: 99%